GRP-186 The Quality of Oral Chemotherapy Prescribing in Oncohaematologial Outpatients. (12th March 2013) - Valero, S; Marrero, P; Lorente, L; Gil, I; Monte, E; Poveda, JL
Abstract : Background: Nowadays, in our health area, most of the oral antineoplastic drugs prescribed to outpatients are dispensed in hospital pharmacy services. Patients receiving these kinds of drugs are susceptible to suffering adverse events (AE) due to medicines errors (MEs). Purpose: To evaluate the quality of oral chemotherapy drug prescriptions (OCDPs) in oncohaematological outpatients. Materials and Methods: Descriptive prospective study. OCDPs for adult patients received in a pharmaceutical outpatient care unit were analysed for two months. The information necessary for OCDPs was established based on legal rules and international recommendations. We established that omitted or confused information in patient identification (identification number), weight, height and/or corporal surface (in drugs dosed depending on these parameters), diagnosis, treatment duration, dose and frequency of administration, presented serious risk based on possible consequences. Results: 291 prescriptions were analysed from 183 patients. 100% of prescriptions had almost one omission, 78.7% of which showed serious errors of omitted or confused information related to the following items: patient identification (0.7%), weight, height or corporal surface (56.7%), diagnosis (28.9%), treatment duration (14.1%), dose (5.8%) or frequency (12.1%). Information omitted or confused about patient and treatment information included: age or birth date (1.4%), allergies (omitted 56%, unknown 38.8%), morbidities (59.5%), cycle number (67%) and periodicity (46.7%). Drug information omitted or confused included: drug name (generic 35.7%, originator 61.5% or both 2.7%), dose units (10.7%), pharmaceutical form (83.1%) or route of administration (58.4%). Physician information omitted or confused included: name (7.6%), signature (1%) and collegiate number (1%). Conclusions: Our results show a high rate of omitted and confused information in prescriptions in OCDP. Extreme attention during the validation process was required in order to prevent MEs and AEs. New tools, such as electronic prescription, pre-printed medical orders or educational programmes for prescribers, must be implemented in order to improve the quality of OCDP. No conflict of interest.